Ariadne’s Journey to Olympus: Reflections of the Myth in the Iconographic Work - Bailón García, Marta (Eikón / Imago, 2018)
Theseus volunteered as a victim accompanying the sacrifice of young people offered by the Aegeus, king of Athens, to Minos, king of Crete. The purpose of the offer was to end the threat of the Minotaur, the final recipient of human sacrifice. Before facing the monster Theseus finds Ariadne, who offered her help to get out of the company unharmed, after promising eternal love. After leaving triumphant, Theseus boarded his ship taking Ariadne with him, but abandoned it on the island of Naxos. There the god Dionysus discovered her and decided to marry her and turn her into a goddess. The myth of Ariadne has been reflected in classical art creating iconographic models that were repeated throughout the Greco-Roman period. After these models were repeated in different representations, adapting to Christianity, as we showed in the example of “Mary Magdalene in the desert”. Equally, the myth of Ariadne continued to be represented with different interpretations.